Licence to be bad : how economics corrupted us - Aldred, Jonathan (2019)
'It is going to change the way in which we understand many modern debates about economics, politics, and society' Ha Joon Chang, author of 23 Things They Don't Tell You About Capitalism Over the past fifty years, the way we value what is 'good' and 'right' has changed dramatically. Behaviour that to our grandparents' generation might have seemed stupid, harmful or simply wicked now seems rational, natural, woven into the very logic of things. And, asserts Jonathan Aldred in this revelatory new book, it's economics that's to blame.Licence to be Bad tells the story of how a group of economics theorists changed our world, and how a handful of key ideas, from free-riding to Nudge, seeped into our decision-making and, indeed, almost all aspects of our lives. Aldred reveals the extraordinary hold of economics on our morals and values. Economics has corrupted us. But if this hidden transformation is so recent, it can be reversed. Licence to be Bad shows us where to begin.
1. The shape of things to come -- 2. Trust no one -- 3. Wealth beats justice: The Curious Coase Theorem -- 4. The government enemy -- 5. Free-riding, or not doing, your bit -- 6. The economics of everything -- 7;. Everyone has a price -- 8. Trust in numbers -- 9. You deserve what you get -- 10. A troubled relationship: modern economics and us.
Includes bibliographical references and index.
Keywords: Ethics